Examining The Diabetic Patient's Awareness of Their Conditions and Physical Activity Level in Saudi Arabia - Alhur, Afrah; Alshamri, Arwa S.; Alhur, Anas; Alanazi, Dalal Nabit; Zaid, Maram Mohammad (The Indonesian Institute of Science and Technology Research, 2023)
Over the past decade, thousands of research described the effects of increased physical activity on diabetic patients. Diabetes mellitus (DM) is considered one of the most chronic diseases that face humankind; it is a severe and long-term condition with a significant impact on the lives and well-being of individuals, families, and societies worldwide. The study participants comprised 41 males and 59 females. Their age ranged from less than 18 to more than 51. We asked the participants how old they were when they were diagnosed with diabetes. Their responses were % in 36-50 and followed by 53%. Our result shows that the first-degree kinship was 36%, and the Second-degree kinship was 51%. Our study indicated that recent studies show that Saudi populations have a high level of diabetic disease among Saudi individuals. Our results confirm that half of them have Second-degree kinship regarding the diabetic's history of DM, and diabetes is relevant among KSA individuals. The majority of the respondents are using insulin as their treatment. Furthermore, 57% lack knowledge of who got the DM. Additionally, we found that those who are inactive in their lives are 50%, while those who are highly active are 8%.